Answer:
(a+b)^2+(a-b)^2=2(a^2+b^2)
expanding:
a² + 2ab + b² + a² -2ab + b² = 2a² + 2b²
2a² + 2b² = 2a² + 2b²
Answer:
x = -16 or x = 6
Step-by-step explanation:
To find the roots of a polynomial function, set the polynomial equal to zero and solve for x.
x² + 10x - 96 = 0
We need to factor the left side. The left side is a quadratic polynomial whose first coefficient is 1. We need two numbers whose product is -96 and whose sum is 10. The numbers are 16 and -6.
(x + 16)(x - 6) = 0
If a product of two factors equals zero, then one factor or the other or both must equal zero.
x + 16 = 0 or x - 6 = 0
x = -16 or x = 6
We don’t see nothing or no image
Answer:
x >= 0 & y<0
x >= 0 means that x is non-negative
y<0 means that y is negative